2022
DOI: 10.3390/antibiotics11050642
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Post-Prescription Review and Feedback Antimicrobial Stewardship Program in Lebanon

Abstract: Antimicrobial stewardship programs (ASPs) are effective means to optimize prescribing practices. They are under-utilized in the Middle East where many challenges exist for ASP implementation. We assessed the effectiveness of infectious disease physician-driven post-prescription review and feedback as an ASP in Lebanon. This prospective cohort study was conducted over an 18-month period in the medical, surgical, and intensive care units of a tertiary care hospital. It consisted of three phases: the baseline, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Results of several studies suggest post-prescription review and feedback AMS programs are effective in both HICs and LMICs [ 5 , 12 ], and could be more acceptable than restrictive strategies [ 20 ]. For the purpose of this study, we conducted further analyses on data collected through our previous study, with the objective of determining if enabling and restrictive AMS strategies operating in our context were associated with different outcomes in terms total antimicrobial usage, MRSA and CRE rates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of several studies suggest post-prescription review and feedback AMS programs are effective in both HICs and LMICs [ 5 , 12 ], and could be more acceptable than restrictive strategies [ 20 ]. For the purpose of this study, we conducted further analyses on data collected through our previous study, with the objective of determining if enabling and restrictive AMS strategies operating in our context were associated with different outcomes in terms total antimicrobial usage, MRSA and CRE rates.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Shallal et al published in Antibiotics evaluated the impact of a post-prescription review and feedback AMS program operating in a tertiary-care hospital in Lebanon [ 12 ]. The authors found the intervention engaged physicians in discussions, provided a platform for education, and fostered collaborative decision-making concerning antibiotic prescription.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the variables monitored by the PPS-2 study and related to the hospital's structure, personnel and organization of IPC activities, we selected the ones potentially acting as determinants of the aforementioned outcomes [11]. A review of the available literature led to considering the following candidate determinants: percentage of single-bed rooms [12][13][14][15], percentage of airborne-infection isolation rooms [13,16], annual alcohol-based hand rub (ABHR) consumption [17,18], proportion of healthcare workers bringing the ABHR dispenser [19] (dichotomized into ≤ 25% vs > 25% as per the multiple choices provided by the PPS-2 form), number of blood cultures per 100 beds [20], number of fulltime equivalent (FTE) nurses [21][22][23], IPC physicians [24][25][26] and antibiotic consultants per 100 beds [27], routine production of an IPC plan [28] and an IPC report [6,7], number of HAI surveillances [29][30][31] and of HAI prevention measures [32], presence of antimicrobial stewardship programmes [24,33] and routine performance of a post-prescription review of antibiotic therapies [34,35]. Data for all these determinants were retrieved from the hospital-level questionnaire form of the PPS-2, except for the proportion of single-bed rooms and ABHR consumption, which were based on data provided through the ward-level forms.…”
Section: Database Buildingmentioning
confidence: 99%
“…We are now seeing a growth in antimicrobial stewardship programs (ASPs) in hospitals across countries and continents to address concerns with inappropriate prescribing [63,69,70]. These include addressing concerns with extended prophylaxis beyond the first day to prevent SSIs and reducing excessive prescribing of antibiotics generally within hospitals [63,69,71,72].…”
Section: Introductionmentioning
confidence: 99%